A Glance at Growth Accounting: Cobb-Douglas Model for G-7 (1950-2018) - İzgi, Berna Balcı; Karadağ, Hande; Beceren, Ertan (European Journal of Digital Economy Research, 2014)
In this article, we inspected the impact of human capital on economic growth by estimating a Cobb-Douglas model for G-7 countries during (1950-2018). Our results show that, human capital has a positive impact on economic growth in the long-run with a contribution of 0.44% whereas evidence is only found for physical capital for the short-run. While the current data for G-7 with the application of pmg reveals that tfp was insignificant.
Keywords: Human Capital; Cobb-Douglas Production Function; Growth; PMG